Natural Fiber@MXene‐Engineered Chitosan Aerogels: Thermodynamic‐Transport Synergy for Solar‐Driven Hypersaline Interfacial Evaporation - Qin Su; Haidi Wu; Suyang Hou; Liping Ye; Yifan Feng; Longjuan Lu; Biwang Pan; Wancheng Gu; Longcheng Tang; Xuewu Huang; Huaiguo Xue; Jiefeng Gao (Advanced Science)
Abstract Enhancing interfacial evaporation rates and optimizing energy utilization remain critical challenges in solar‐driven steam generation. Natural fiber@MXene‐engineered chitosan aerogels with hierarchically oriented channels to achieve high‐efficiency solar‐driven steam generation are developed. The kapok fiber@MXene core–shell units (MKFs) construct photon‐entrapping topological networks that enhance light absorption while simultaneously reinforcing the aerogel's structural integrity and durability for practical applications. The aerogel's oriented microchannels establish thermodynamic potential gradients, facilitating spontaneous capillary‐driven water replenishment and environmental thermal harvesting. Both experimental results and COMSOL multiphysics simulations systematically demonstrate that hierarchical pore channels enhance water transport, improve solar‐thermal/environmental energy synergy, and promote the downward diffusion of concentrated ions from the evaporation surface, achieving an evaporation rate up to 4.40 kg m−2 h−1 with efficient salt rejection. Long‐term outdoor tests with various corrosive wastewater solutions further validate the aerogel's durability in solar‐driven interfacial evaporation. This study provides a theoretical foundation for understanding the interrelation between solar energy absorption, water transport, and salt diffusion in aerogel evaporators with hierarchical fiber‐pore architectures.